Effect of geographical variation of Echis ocellatus, Naja nigricollis and Bitis arietans venoms on their neutralization by homologous and heterologous antivenoms. (15th December 2015) - Sánchez, Andrés; Coto, Jorge; Segura, Álvaro; Vargas, Mariángela; Solano, Gabriela; Herrera, María; Villalta, Mauren; Estrada, Ricardo; Gutiérrez, José María; León, Guillermo
Abstract: Two antivenoms prepared by using Echis ocellatus, Bitis arietans and Naja nigricollis venoms from different locations in sub-Saharan Africa were compared for their neutralizing ability. Both antivenoms were similarly effective in the neutralization of the venoms of the three species from different locations. However in the case of E. ocellatus venom, antivenom prepared using venom from Nigerian specimens was more effective than antivenom prepared with venom from Cameroon specimens in the neutralization of coagulant activity. Highlights: Antivenoms towards venoms from different locations were prepared and compared. Both antivenoms were effective towards venoms from different locations. Neutralizing activity was affected by intraspecific variations on venom.